An Empirical Study of Mutual Funds Performance and Performance Persistence-The Case of China - CHEN, CHAO (2012)
Abstract The increasing popularity of mutual funds investment is a remarkable phenomenon of recent decades; investors pay more and more attention on the issues of the mutual funds’ performance and the performance persistence. Meanwhile, China’s mutual funds market blossomed recently , although the market in China is less mature than the U.S or other developed mutual funds market, its dramatically development also captures the global investor’s notice. Therefore, this paper mainly examined recent performance of 30 China mutual funds held by different mutual funds companies during the period from January 2008 to December 2010. The issues of risk-adjusted performance and performance persistence are addressed. We employ both single-factors and multi-factors models to evaluate the monthly return on the sample funds relative to the performance of the China market benchmark. Performance persistence of China mutual funds are assessed at three-month, six-month and one-year intervals respectively based on their ranking and evaluation periods through cross-sectional regression t-test. As a result, we find no obvious significant performance persistence in both short run and long run in China mutual funds market.